Teachers' enactments of curriculum: Fidelity to Procedure versus Fidelity to Goal for scientific argumentation. Issue 12 (13th August 2018) - McNeill, Katherine L.; Marco-Bujosa, Lisa M.; González-Howard, María; Loper, Suzanna
ABSTRACT: Fidelity of implementation (FOI) has received attention in calls for funding and research; however, there are numerous ways of conceptualising and measuring this construct. We argue that this conceptualisation is important for recent reform efforts focused on science practices. Consequently, we explored FOI in the context of the enactment of a middle-school curriculum focused on one particular science practice, argumentation. We coded videos of five teachers' enactments of argumentation lessons using two different fidelity coding schemes. First, Fidelity to Procedure targeted teachers' adherence to the order and types of procedures. Second, Fidelity to Goal examined teachers' adherence to the overarching argumentation goals. This analysis resulted in case studies that illustrate distinct patterns in the teachers' curriculum enactments. One case in particular, Ms Newbury, received a low score for Fidelity to Procedure, but a high score for Fidelity to Goal . She altered procedures to provide her students, all of whom were English Language Learners, with different linguistic supports, but maintained the overarching argumentation goals. Consequently, we argue that FOI for goals may better capture whether teachers' enactments are supporting students in the science practices. Furthermore, the results suggest the importance of educative curriculum including rationales for the curricular goals.